Microstrip dual J-shape monopole for material characterization / Zainal Abidin Ali Zahari - Ali Zahari, Zainal Abidin (2013)
Throughout this thesis, it will briefly describe the design of dual J-shape bend monopoles in microstrip circuit, The microstrip dual monopole was design and analayze using computer simulation technology software.